E-Marketing and Product Reviews on Purchasing Decisions in the Culinary Creative Industry (Case Study: Chili Derivative Business) - Syera, Inda Arfa; Affiah, Hajar (International Journal of Economics (IJEC), 2024)
The aim of this research is to determine the influence of E-Marketing and Product Reviews on Product Purchasing Decisions in Chili Derivative Businesses in Lubuk Cuik Village. The approach used in this research is a quantitative approach. The data used in this research is primary data sourced from questionnaires. The analysis techniques used are classical assumption tests (normality test, multicollinearity test and heteroscedasticity test), multiple linear regression, and hypothesis testing (F statistical test, and t statistical test, as well as the coefficient of determination (R2) test). The results of this research are based on the results of a simultaneous test (f test), it can be seen that the E-Marketing and Product Review variables have a significant effect together (simultaneously) on the Purchasing Decision variable. Based on the partial test, the E-Marketing variable has a positive and significant effect on product purchasing decisions at chili derivative businesses in Lubuk Cuik Village and the Product Review variable has a positive and significant effect on product purchasing decisions at chili derivative businesses in Lubuk Cuik Village.